Anammox bacteria enrichment in upflow anaerobic sludge blanket (UASB) reactor - Thuan, TH; Jahng, DJ; Jung, JY; Kim, DJ; Kim, WK; Park, YJ; Kim, JE; Ahn, DH (KOREAN SOC BIOTECHNOLOGY & BIOENGINEERING, 2004)
We investigated the anaerobic ammonium oxidation (anammox) reaction in a lab-scale upflow anaerobic sludge blanket (UASB) reactor. Our aim was to detect and enrich the organisms responsible for the anammox reaction using a synthetic medium that contained low concentrations of substrates (ammonium and nitrite). The reactor was inoculated with granular sludge collected from a full-scale anaerobic digester used for treating brewery wastewater. The experiment was performed during 260 days under conditions of constant ammonium concentration (50 mg NH4+-N/L) and different nitrite concentrations (50similar to150 mg NO2-N/L). After 200 days, anammox activity was observed in the system. The microorganisms involved in this anammox reaction were identified as Candidatus B. Anammoxidans and K. Stuttgartiensis using fluorescence in situ hybridization (FISH) method.
Keywords: AMMONIUM-OXIDIZING BACTERIA; OXIDATION